Reception and medical and biologic tests marked by 99mTc norfloxacin of the hydrochloride - N. V. Varlamova; V. S. Scuridin; S. I. Sazonova (Бюллетень сибирской медицины)
Are carried out researches on creation of a standard reagent for reception marked by 99mТс Norfloxacine hydrochloride. An estimation of influence of components of a reactionary mix on radiochemical cleanliness of a received preparation spent a method for thin-layer chromatographies. On experimental animal (rabbits) with model of an inflammation of various localization functional suitability marked by an antibiotic for diagnostics of inflammatory processes is shown.